Stress Resilience of Spermatozoa and Blood Mononuclear Cells without Prion Protein - Reiten, Malin R.; Malachin, Giulia; Kommisrud, Elisabeth; Østby, Gunn C.; Waterhouse, Karin E.; Krogenæs, Anette K.; Kusnierczyk, Anna; Bjørås, Magnar; Jalland, Clara M. O.; Nekså, Liv Heidi; Røed, Susan S.; Stenseth, Else-Berit; et al. (Frontiers in Molecular Biosciences, 2018)
The cellular prion protein PrPC is highly expressed in neurons, but also present in non-neuronal tissues, including the testicles and spermatozoa. Most immune cells and their bone marrow precursors also express PrPC. Clearly, this protein operates in highly diverse cellular contexts. Investigations into putative stress-protective roles for PrPC have resulted in an array of functions, such as inhibition of apoptosis, stimulation of anti-oxidant enzymes, scavenging roles and a role in nuclear DNA repair. We have studied stress resilience of spermatozoa and peripheral blood mononuclear cells (PBMCs) derived from non-transgenic goats that lack PrPC (PRNPTer/Ter) compared with cells from normal (PRNP+/+) goats. Spermatozoa were analyzed for freeze tolerance, DNA integrity, viability, motility, ATP levels and acrosome intactness at rest and after acute stress, induced by Cu2+ ions, as well as levels of reactive oxygen species (ROS) after exposure to FeSO4 and H2O2. Surprisingly, PrPC-negative spermatozoa reacted similarly to normal spermatozoa in all read-outs. Moreover, in vitro exposure of PBMCs to Doxorubicin, H2O2 and methyl methanesulfonate (MMS), revealed no effect of PrPC on cellular survival or global accumulation of DNA damage. Similar results were obtained with human neuroblastoma (SH-SY5Y) cell lines stably expressing varying levels of PrPC. RNA sequencing of PBMCs (n = 8 of PRNP+/+ and PRNPTer/Ter) showed that basal level expression of genes encoding DNA repair enzymes, ROS scavenging and antioxidant enzymes were unaffected by the absence of PrPC. Data presented here questions the in vitro cytoprotective roles previously attributed to PrPC, although not excluding such functions in other cell types or tissues during inflammatory stress.